2020
DOI: 10.1038/s41467-019-13672-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast charge ordering by self-amplified exciton–phonon dynamics in TiSe2

Abstract: The origin of charge density waves (CDWs) in TiSe has long been debated, mainly due to the difficulties in identifying the timescales of the excitonic pairing and electron–phonon coupling (EPC). Without a time-resolved and microscopic mechanism, one has to assume simultaneous appearance of CDW and periodic lattice distortions (PLD). Here, we accomplish a complete separation of ultrafast exciton and PLD dynamics and unravel their interplay in our real-time time-dependent density functional theory simulations. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 115 publications
(112 reference statements)
4
57
1
Order By: Relevance
“…The results showed that the PLD and excitonic orders are coupled in 1T-TiSe 2 , consistent with theoretical results which invoked a cooperative J-T effect and excitonic order [22]. In fact, in a very recent theoretical study using real-time time-dependent density functional calculations, it was concluded that the excitonic order and PLD mutually amplify each other, resulting in the CDW transition [23].…”
Section: Introductionsupporting
confidence: 85%
“…The results showed that the PLD and excitonic orders are coupled in 1T-TiSe 2 , consistent with theoretical results which invoked a cooperative J-T effect and excitonic order [22]. In fact, in a very recent theoretical study using real-time time-dependent density functional calculations, it was concluded that the excitonic order and PLD mutually amplify each other, resulting in the CDW transition [23].…”
Section: Introductionsupporting
confidence: 85%
“…The major disagreement between the two mechanisms previously proposed: electron–EPC and excitonic paring, lies on the explicit roles of periodic lattice distortions (PLD) in forming the CDW. We adopt the newly developed rt‐TDDFT method to perform quantum photoexcitation simulation of TiSe 2 under laser pulses, in order to specify a detailed atomic mechanism for the ultrafast CDW dynamics 39 …”
Section: Applicationsmentioning
confidence: 99%
“…The laser pulse melts charge order within 20 fs, producing the forces that trigger the ionic movements. The self‐amplified dynamics is assisted by electron–phonon couplings after initial excitation (Reprinted with permission from Reference 39. Copyright 2019 Springer Nature)…”
Section: Applicationsmentioning
confidence: 99%
“…Titanium dichalcogenides TiCh 2 (Ch = S, Se, Te) have been studied for a long time. [1][2][3][4][5][6] The intercalation of 3d transition metals into TiCh 2 alters significantly the physical properties and electronic structure of these materials. [7][8][9][10] To date, the effect of intercalation on the electronic structure of layered transition metal dichalcogenides is well understood.…”
Section: Introductionmentioning
confidence: 99%